1960
DOI: 10.1149/1.2427827
|View full text |Cite
|
Sign up to set email alerts
|

The Silver-Silver Oxide Electrode

Abstract: An a‐c square wave technique was used to study resistance and double‐ layer capacity during film formation on silver electrodes in KOH solutions. The peak in the voltage‐time curve at constant current anodization is shown to coincide with complete surface coverage by Ag2O and is not an ohmic resistance, but rather an overvoltage effect. Evidence for the existence of an unstable higher oxide than normalAgO (or additional oxygen) during oxygen evolution is presented. Microvolumetric gas measurements with l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
45
0

Year Published

1969
1969
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 61 publications
(53 citation statements)
references
References 5 publications
8
45
0
Order By: Relevance
“…6, a roughness factor of approximately 200 must be assumed for an electrode which is reduced electrochemically. For comparison purposes, polarization curves for electrodes etched in 1 : 1 nitric acid were similarly analyzed, and led to roughness factors of 15 to 20, in good agreement with those reported by Cahan et al (24) for silver treated in this manner. There seems to be no reason, therefore, to reject the roughness factor value of 200 for electrochemically reduced electrodes.…”
Section: Effect Of Electrode Treatmentsupporting
confidence: 81%
“…6, a roughness factor of approximately 200 must be assumed for an electrode which is reduced electrochemically. For comparison purposes, polarization curves for electrodes etched in 1 : 1 nitric acid were similarly analyzed, and led to roughness factors of 15 to 20, in good agreement with those reported by Cahan et al (24) for silver treated in this manner. There seems to be no reason, therefore, to reject the roughness factor value of 200 for electrochemically reduced electrodes.…”
Section: Effect Of Electrode Treatmentsupporting
confidence: 81%
“…Dirkse [19] suggested that the peak is due to a maximum ohmic potential drop associated with a complete film of Ag20. Cahan et al [22] concluded from measurements of the resistance of the Ag20 layer that the peak is not directly due to an ohmic resistance effect but to concentration of the current in small localized areas, where the conversion of Ag20 to AgO can proceed. Yoshizawa and Takehara [24] believed that the peak is generated because 02-ions can diffuse more easily in the AgO layer than in the Ag20 layer.…”
Section: Galvanostatic Measurementsmentioning
confidence: 99%
“…The reference electrode was a mercury/mercuric oxide electrode prepared a s described by Cahan et a/. (9). It was located in a compartment which contained a 20% aqueous solution of ammonium pentaborate.…”
Section: Tlie Cell a R~d Electrodesmentioning
confidence: 99%
“…Accordingly, [14] may be written which on using the boundary conditions [I 11 and [I 51 (i.c. P,(Q = 0) = coxkE,, k = 2, 3) may be integrated to yield the following expression for P, From [6] and [ l l ] , BE, = BSE2 for Q > 0 , so that [5] may be written Eliminating P and then PI using [13] and [9], and eliminating using [7] gives Substituting for P2 and P, from [A51 leads to an integral equation in E. Elimination of the two integrals by the usual method of isolation and differentiation leads to the following second order differential equation in the excess field, A E = E -E 2 .…”
Section: Decliy Rynf Excess Fieldmentioning
confidence: 99%